Production of perdeuterated fucose from glyco-engineered bacteria. (27th June 2020) - Gajdos, Lukas; Forsyth, V Trevor; Blakeley, Matthew P; Haertlein, Michael; Imberty, Anne; Samain, Eric; Devos, Juliette M
Abstract: l -Fucose and l -fucose-containing polysaccharides, glycoproteins or glycolipids play an important role in a variety of biological processes. l -Fucose-containing glycoconjugates have been implicated in many diseases including cancer and rheumatoid arthritis. Interest in fucose and its derivatives is growing in cancer research, glyco-immunology, and the study of host–pathogen interactions. l -Fucose can be extracted from bacterial and algal polysaccharides or produced (bio)synthetically. While deuterated glucose and galactose are available, and are of high interest for metabolic studies and biophysical studies, deuterated fucose is not easily available. Here, we describe the production of perdeuterated l -fucose, using glyco-engineered Escherichia coli in a bioreactor with the use of a deuterium oxide-based growth medium and a deuterated carbon source. The final yield was 0.2 g L −1 of deuterated sugar, which was fully characterized by mass spectrometry and nuclear magnetic resonance spectroscopy. We anticipate that the perdeuterated fucose produced in this way will have numerous applications in structural biology where techniques such as NMR, solution neutron scattering and neutron crystallography are widely used. In the case of neutron macromolecular crystallography, the availability of perdeuterated fucose can be exploited in identifying the details of its interaction with protein receptors and notably the hydrogen bonding network around the carbohydrate binding site.